A New Global Automotive Industry - Kierzkowski, Henryk (Journal of Public Governance, 2010)
The global automotive sector will experience groundbreaking changes over the coming decades. The number of carowners will increase significantly, especially in developing countries such as China and India, where new factories are established or moved from Europe and the US. Electric cars will probably have an important share of the market because of the growing public concern for climate change, the diminishing supply of oil and better car batteries. Much of the anticipated radical change in automotive technologies will occur outside the traditional automotive sector, with products such as new potent batteries and capacitators. The cost of maintenance of the new cars will be much lower than of traditional vehicles. The changes in the automotive sector will likely be supported by the governments of China and India. The article proposes some of the actions that should be undertaken.